Prins-pinacol synthesis of a variety of highly functionalized bicyclo[4n1]alkanones - Lavigne, Roch M. A (University of Ottawa (Canada), 2006)
Bridged ring cores possessing quaternary carbon centers adjacent to a bridged ketone constitute challenging structures in synthesis. Therefore, this thesis explores the development of the first Prins-pinacol synthesis of cis-fused bicyclo[4,n,1]alkanones. The reaction conditions were optimized for the rearrangement of bicyclo[4.4.0]decanes and the effect of different diol protecting groups was explored, as well as the effect of substitution at the C4 and the C5 position. The rearrangement of bicyclo[5.4.0]undecane and bicyclo[5.3.0]decanes was also investigated in order to achieve the formation of bicyclic ketones with various ring sizes. Finally, the Prins-pinacol rearrangement was coupled with an ionic Diels-Alder reaction in order to achieve the rapid synthesis of highly functionalized polycyclic bridgehead ketones.
Keywords: Chemistry, Organic.